Enhanced Biodegradation of Hydrocarbons in the Rhizosphere of Plant Species in Semi-Arid Regions - Shirdam, Ravanbakhsh; Daryabeigi Zand, Ali; Nabibidhendi, Gholamreza; Mehrdadi, Nasser (Asian Journal of Chemistry, 2010)
High amounts of industrial activities related to oil extraction, purification and transportation in Iran, as an important oil producing country in the world, have caused serious forms of pollution with oil products, particularly near oil refineries. To date, many developing countries like Iran have almost completely relinquished remediation of oil-polluted soils due to the high costs of conventional (physical/chemical) soil remediation methods. Phytoremediation is an emerging green technology that can be a promising solution to remediate hydrocarbon-polluted soils. Screening native tolerant plant species for growing on aged, petroleum hydrocarbon-contaminated soils is a key factor for successful phytoremediation. This study investigated the effect of hydrocarbon pollution with initial concentration of 40000 ppm on growth characteristics of burningbush [Kochia scoparia (L.) Schard] and flax (Linum usitatissumum L.). At the end of the experiment, soil samples in which plant species grown well were analyzed for total petroleum hydrocarbons (TPHs) removal by GC-FID. Heterotrophic bacteria and hydrocarbondegrading bacteria in the samples were determined as well. In the current research, burningbush was used for the first time in the history of phytoremediation in the world. Burningbush and flax showed promising remediation efficiency in highly contaminated soil. However, petroleum hydrocarbon contamination depressed growth of surveyed plants significantly. Flax reduced TPHs concentration by 35000 mg/kg.